Light Energy: Our Wasted Resource - Tatro, Kaitlyn (Consilience, 2020)
Artificial light at night (ALAN) is a form of visual pollution and energy waste that is often overlooked. The International Dark Sky Association estimates that 30% of all lighting is strictly for the outdoors. Furthermore, 30% of all outdoor lighting is wasted, used (1) when not needed, or (2) pointing directly upwards. In 2017, the US wasted approximately 60 billion kilowatt hours (kWh), translating to a loss of more than $6.3 billion and CO2 emissions in excess of 23 billion pounds. ALAN has been linked to reduced production of melatonin, the body’s sleep-regulating hormone, which is associated with increased risk of hormonal cancers including breast and prostate cancer. In fact, the World Health Organization (WHO) now lists shift work as a type II risk for cancer. Light at night threatens migratory birds, a majority of which fly at night presumably using constellations as their guide. Light pollution paints the sky black, pushing astronomers to ever-shrinking dark zones suitable for studying the universe. In the most severely affected cities, only a handful of stars can be seen where once thousands dazzled gazers. Society’s overreliance on ALAN has resulted in energy waste, adverse health effects, and pervasive pollution contributing to climate change and concealing our starry night sky.